Work Becomes Obligation for the Family: Analysis of Work-Family Balance on Fishermen's Wife - Sri Rahayu (International Journal of Social Science and Business, 2020)
This study aims to reveal the experiences of fishermen's wives working in balancing the dual roles of work and family, as well as the factors that can influence it. This study uses a qualitative method with a phenomenological approach. The data analysis technique in this research uses the Interpretative Phenomenological Analysis (IPA) technique. The researcher managed to conclude that there were five main themes including; a picture of life at work, the dynamics of life in the family, a picture of life undergoing multiple roles, the factors that influence the dual role of fishermen's wives and exploration of achieving balance in playing multiple roles. The role of being a housewife in a family and working to help the family economy begins when fishermen's wives choose to work after marriage. The encouragement of fishermen's wives to keep working after marriage is due to uncertain family income. This is also because their husband's catch depends on the season. Erratic season affects the fishermen's catch. One of the encouragement of fishermen's wives to work is to actualize their potential and abilities and to meet family needs